1903 Mont. Laws at 49 Ch. 35, § 3 - (:unkn) unknown (General Publisher, 1903)
Prohibited entering any church, religious assembly, school room, or other place where persons are assembled for amusement or for educational or scientific purposes, or into any circus, show, or public exhbition of any kind, or into a ball room, socila party, or social gathering, or to any election precinct or any place of registration, on the day or days of any election or registration, where people of the State are collected to register or vote on any election. Prohibited weapons included pistol, other firearms, dirk, dagger, slung shot, sword cane, knuckles, or Bowie knife. Violators punished by not less than fifty nor more than five hundred dollars.
--
Keywords: SENSITIVE PLACES